Aktivitas Fisik Berjalan Kaki terhadap Pencegahan Penyakit Tidak Menular (Noncommunicable disease) : Literatur Review - Iriyani Harun (Preventia : The Indonesian Journal of Public Health, 2020)
Non-communicable diseases are chronic diseases that tend to last longer and are the result of a combination of genetic, environmental and lifestyle factors that show increasing numbers and are the number one cause of death in the world. One of the factors that cause the increasing prevalence of NCD is physical inactivity to contribute to global death and is expected to continue to increase. In Indonesia, the inactive condition also has increased so that it has a higher risk of suffering from cardiovascular diseases such as hypertension, obesity, hypercholesterolemia, and several other diseases.Walking is one form of simple physical activity that can be accessed by everyone and is beneficial to health, but research related to increasing physical activity, especially walking for handling non-communicable diseases is still very limited, especially in Indonesia. This review article aims to present some information related to the benefits of physical activity, especially walking as an effort to deal with the problem of non-communicable diseases such as hypertension, hypercholesterolemia, and obesity. The study method was conducted on several articles obtained from online search results through, Scopus, PubMed, Google Scholar, Science Direct, published in the last 10 years with keywords walking, physical activity, hypertension, lipid profile, obesity. The results of the study showed that walking interventions and dietary changes had a significant influence on the prevention of non-communicable diseases such as hypertension, hypercholesterolemia, and obesity. Components of walking exercise interventions such as frequency, duration, and intensity are the main keys to the success of the intervention. The review provided can be useful as one of the health promotion strategies to increase daily physical activity and reduce chronic illness in inactive adults.